Quantitative real-time PCR method to detect changes in specific transcript and total RNA amounts - Baek, Kwang-Hyun; Skinner, Daniel Z. (Electronic Journal of Biotechnology, 2004)
Quantitative real-time PCR (qRT-PCR), used in conjunction with reverse transcriptase, has been applied to the determination of the number of copies of a transcript per unit mass of RNA, but did not indicate any change in the amount of total RNA per mass of tissue. In the present work, we described a simple method to use qRT-PCR to estimate the change in the amount of total RNA per unit mass of wheat (Triticum aestivum L.) tissue in response to cold temperature. Three qRT-PCR templates, i.e. control, cold-exposed, and one of RNA extracted from a sample consisting of equal masses of control and cold-exposed tissue, were analyzed. The number of copies of target transcript per unit mass of RNA was estimated from the three samples using standard qRT-PCR techniques. Equations describing the number of copies of the target sequence in each of the tissue samples were solved simultaneously to describe the relative proportion of the target sequence that originated from each tissue sample in the mixture, thereby providing an estimate of relative amounts of total RNA in the two tissues.